Arterial hypertension and antihypertensive therapy in older patients. The agreed opinion of experts from the Russian Association of Gerontologists and Geriatricians, the Antihypertensive League, the National Society for Preventive Cardiology - O. N. Tkacheva; Yu. V. Kotovskaya; N. K. Runikhina; E. V. Frolova; V. S. Ostapenko; N. V. Sharashkina; E. I. Baranova; S. V. Bulgakova; S. V. Villevalde; D. V. Duplyakov; A. N. Ilnitskiy; O. A. Kislyak; et al. (Рациональная фармакотерапия в кардиологии, 2021)
High blood pressure is a risk factor for cardiovascular morbidity and mortality, as well as cognitive decline and loss of autonomy in the elderly and old age. Randomized clinical trials (RCTs) in populations of older patients living at home with low comorbidity and preserved autonomy indicate the benefit of lowering elevated blood pressure in patients over 80 years of age. Older patients with senile asthenia, loss of autonomy and other geriatric problems were excluded from RCTs, and observational studies in these groups of patients indicate an increase in morbidity and mortality with lower blood pressure and antihypertensive therapy. Obviously, in very elderly patients, a universal strategy for the treatment of arterial hypertension cannot be applied due to the significant heterogeneity of their functional status. The geriatric approach to the management of arterial hypertension in older patients involves an assessment of the functional status, the presence of senile asthenia, and the degree of autonomy for the choice of antihypertensive therapy tactics.